EFFECT OF PROBLEM BASED: LIFE-LONG EDUCATION IN INDUSTRIAL AND DEVELOPING COUNTRIES - Nurlela Baco; Elihami Elihami (JURNAL EDUKASI NONFORMAL, 2021)
To explore how well graduates of self-directed, problem-based undergraduate curricula (USA, Vietnam, Taiwan, RRC, and Japan) who go on to primary care careers adhere to current clinical practice guidelines. Lifelong education is education that does not stop until it becomes an individual to become an adult, but continues throughout life. Lifelong education is of higher urgency at this time because humans need to continually adjust themselves so that they live naturally in an ever changing society. Lifelong education in industrialized and developing countries is indispensable in order to increase equality in the distribution of educational services, has pleasant economic implications, and essential in dealing with changing social structures there are vocational reasons for determining it will deliver an increase in the quality of life. Although the concept of lifelong education in industrialized and developing countries is different, the goal remains the same